Elements of Competency for Facility Engineers in The Field of Refrigeration and Air Conditioning - Yunus, Faizal Amin Nur; Rahim, Mohd Bekri; Razali, Mohd Nizamuddin; Abdul Rahman, Khairul Anuar (Online Journal for TVET Practitioners, 2022)
The challenge for institutions of higher learning today is to provide the human capital that this industry desperately needs. Past studies have shown that most graduates of local institutions of higher learning do not have the necessary work skills and competencies in the market and there seems to be mismatch in the preparation of graduates for the local job market. In this regard, universities are often blamed for failing to meet the needs of industry and employers. On this basis, this study is hoped to open further discussion space and can help the parties involved in making improvements to improve the quality of graduates especially producing skilled workforce according to industry demand. This study aims to explore the elements of competency that a facility engineer should have in the field of air conditioning and air conditioning. This study was done to provide a comprehensive overview of the elements of competency that need to be presented to the Facility Engineers in order to help the graduates of the Refrigeration and Air Conditioning Technology course at Universiti Tun Hussein Onn Malaysia (UTHM) to be better prepared for the occupational environment. This study used the Modified Delphi Technique – MDT approach for the purpose of obtaining expert approval on constructs in questionnaire instruments as well as using literature survey study through analysis documents. The research instrument used was a set of questionnaires prepared to obtain evaluation from experts. The data were processed by using Statistical Package for the Social Sciences (SPSS) software to obtain the mean score, median and Interquartile Range (IQR) for each item. The findings of the literature review through document analysis produced ten elements and 64 items. Meanwhile, the findings of the modified Delphi study produced the competence of Facility Engineers which has 10 elements and 62 items.